Three psychologies perspectives from Freud, Skinner, and Rogers - Nye, Robert D. (Wadsworth/Thompson Learning, 2000)
In this revision of his popular & critically acclaimed book, Robert Nye clearly & succinctly presents the essential ideas of Freud, Skinner, & Rogers, three of the most important contributors to contemporary psychological thought. * The author is known for his fair, comprehensive, & above all objective treatment of each of the three theories. "Although the book is concise, it includes all the high points of the major theoretical orientations presented." An epilogue features concise presentations of cognitive psychology & Ellis' rational-emotive behavior therapy. Annotation. Writing primarily for beginning undergraduate students, Nye (formerly psychology, State U. of NY, New Paltz) presents and compares the major ideas of Sigmund Freud, B. F. Skinner, and Carl Rodgers. Devoting the majority of the discussion to theory, he discusses the psychological ideas of psychoanalysis, radical behaviorism, and humanistic phenomenology after brief biographies of their originators.